الكشف المصلي عن الملوية البوابية إيجابية الـCagA عند المرضى المصابين بأمراض معدية عفجية مختلفة - يازجي, هيثم; امطانيوس, ميلاد; غانم, غنوة (Latakia University Journal -Medical Sciences Series, 2013)
هدفت هذه الدراسة إلى معرفة العلاقة بين ذراري الملوية البوابية (HP) إيجابية الـcagA والقرحة المعدية والعفجية وسرطان المعدة الغدي، شملت الدراسة 61 مريضاً مصاباً بعسر الهضم من المرضى المراجعين لقسم التنظير الهضمي في مشفى الأسد الجامعي في اللاذقية، في أثناء التنظير الهضمي العلوي لهم تم أخذ خزعات معدية لإجراء اختبار الـ Clo-testوالفحص النسيجي، ثم سحب الدم للمرضى إيجابتي الـ Clo-testلإجراء الاختبارات المصلية لـ HP و . cagAبعد إجراء التنظير الهضمي العلوي والفحص النسيجي تم توزيع المرضى على 4 مجموعات وهي التهاب المعدة المزمن (28 مريضاً) والقرحة المعدية (5 مرضى) والقرحة العفجية (17 مريضاً) وسرطان المعدة الغدي (11 مريضاً). كانت أضداد الـ CagA إيجابية عند 68.85% من مرضى الدراسة. وقد اختلفت نسبة إيجابية هذه الأضداد بشكل هام إحصائياً بين مجموعات المرضى الأربعة (0.006P = )، فكانت أعلى نسبة إيجابية بين مرضى سرطان المعدة الغدي (90.91%)، ثم القرحة العفجية بنسبة 88.24%، فالقرحة المعدية بنسبة 80%، بينما كانت أقل نسبة إيجابية بين مرضى التهاب المعدة المزمن (46.43%). كما وجدت دراستنا عدم وجود فروق هامة إحصائياً في عيار أضداد الـHP بين المجموعات الأربعة (P = 0.90 )، ولكن هذا العيار كان أعلى عند مرضىcagA+ بالمقارنة بــ cagA- (P = 0.05). خلصت الدراسة إلى وجود علاقة إيجابية بين الـcagA+ والقرحة الهضمية وسرطان المعدة الغدي في سوريا. This study aimed to know the relation between cagA positive Helicobacter pylori (HP) strains and diseases such as gastric and duodenal ulcers and gastric adenocarcinoma. The study included 61 dyspeptic patients from gastrointestinal (GI) endoscopy department patients in Al-Assad university hospital in Lattakia. During upper (GI) endoscopy, gastric biopsy specimens were obtained for Clo-test and histologic examination. Blood was obtained from Clo-test positive patients for serologic tests of HP and cagA. After upper (GI) endoscopy and histologic examination, patients were divided into 4 groups: chronic gastritis (28 patients), gastric ulcer (5 patients), duodenal ulcer (17 patients) and gastric adenocarcinoma (11 patients). CagA antibodies were positive in 68.85% of patients. The difference in the proportion of CagA antibody positive between the four groups was highly significant (P= 0.006). The highest positive proportion was in gastric adenocarcinoma (90.91%) then duodenal ulcer (88.24%) then gastric ulcer (80%), while the lowest positive proportion was in chronic gastritis (46.43%). There was no difference in HP antibody levels between the four groups (P = 0.90) but these levels were significantly higher in cagA+ patients compared to cagA- (P= 0.05). This study found a positive relation between cagA+ and diseases such as peptic ulcer and gastric adenocarcinoma in Syria .